2013
DOI: 10.1097/ccm.0b013e31828e9b03
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized, Double-Blind, Placebo-Controlled, Phase 2b Study to Evaluate the Safety and Efficacy of Recombinant Human Soluble Thrombomodulin, ART-123, in Patients With Sepsis and Suspected Disseminated Intravascular Coagulation*

Abstract: ART-123 is a safe intervention in critically ill patients with sepsis and suspected disseminated intravascular coagulation. The study provided evidence suggestive of efficacy supporting further development of this drug in sepsis-associated coagulopathy including disseminated intravascular coagulation. Future study should focus on using ART-123 in the subgroup of patients most likely to respond to this agent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
232
2
7

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 271 publications
(247 citation statements)
references
References 29 publications
6
232
2
7
Order By: Relevance
“…In the subgroup of patients who did not receive concomitant heparin during the treatment phase, the 28 d mortality was lower in the AT group (37.8%) than in the placebo group (43.6%) but this difference did not reach statistical significance (P = 0.08). This mortality trend, however, became significant after 90 d, 44.9% in the AT group vs 52.5% in the placebo group, suggesting that there might be a role for AT therapy in the absence of heparin.…”
Section: Antithrombinmentioning
confidence: 89%
“…In the subgroup of patients who did not receive concomitant heparin during the treatment phase, the 28 d mortality was lower in the AT group (37.8%) than in the placebo group (43.6%) but this difference did not reach statistical significance (P = 0.08). This mortality trend, however, became significant after 90 d, 44.9% in the AT group vs 52.5% in the placebo group, suggesting that there might be a role for AT therapy in the absence of heparin.…”
Section: Antithrombinmentioning
confidence: 89%
“…The systematic review for this CQ was conducted using 3 RCTs398, 400, 401 as mentioned previously. The quality of evidence was “B” (moderate), and it was determined that the potential benefits likely outweigh the potential risks.…”
Section: Cq16: Diagnosis and Treatment Of Disseminated Intravascular mentioning
confidence: 99%
“…Rationale Most RCTs of recombinant soluble thrombomodulin have been targeted for sepsis associated with DIC, and a systematic review suggested a beneficial effect on survival without an increase of bleeding risk [342,343]. A phase III RCT is ongoing for sepsis associated with DIC.…”
mentioning
confidence: 99%